2004
DOI: 10.1091/mbc.e03-10-0742
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome of Prematurely Aging Yeast Cells Is Similar to That of Telomerase-deficient Cells

Abstract: To help define the pathologies associated with yeast cells as they age, we analyzed the transcriptome of young and old cells isolated by elutriation, which allows isolation of biochemical quantities of old cells much further advanced in their life span than old cells prepared by the biotin-streptavidin method. Both 18-generation-old wild-type yeast and 8-generation-old cells from a prematurely aging mutant (dna2-1), with a defect in DNA replication, were evaluated. Genes involved in gluconeogenesis, the glyoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
95
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 65 publications
(119 reference statements)
10
95
2
Order By: Relevance
“…For example, from population-level metabolomic measurements on cellcycle-synchronized yeast cells, it was found that significant changes in gene regulation and metabolite levels occur during the cell cycle [14]. Also, the age of a yeast cell was argued to influence the metabolic phenotype in clonal cells: In cells that were sorted according to their age, dramatic metabolic differences were found [15][16][17]. Synchronizing as well as sorting cells likely affects the metabolome, due to fast metabolic turnover rates.…”
Section: Why Single Cell Metabolomics?mentioning
confidence: 99%
“…For example, from population-level metabolomic measurements on cellcycle-synchronized yeast cells, it was found that significant changes in gene regulation and metabolite levels occur during the cell cycle [14]. Also, the age of a yeast cell was argued to influence the metabolic phenotype in clonal cells: In cells that were sorted according to their age, dramatic metabolic differences were found [15][16][17]. Synchronizing as well as sorting cells likely affects the metabolome, due to fast metabolic turnover rates.…”
Section: Why Single Cell Metabolomics?mentioning
confidence: 99%
“…In addition, the expression of ribosome genes and genes involved in protein synthesis, folding, and degradation all decreased (14,15). Besides changes in metabolic gene expression, environmental stress response genes were induced in aged cells (7), although oxidative stress gene expression did not change (14). Genes involved in DNA damage repair such as homologous recombination and nucleotide excision repair were also induced in old cells (7,15).…”
mentioning
confidence: 97%
“…Several transcriptome analyses comparing old cells with young cells have shown pathway changes in expression during replicative aging (7,(13)(14)(15). In all cases, a shift from glycolysis toward gluconeogenesis and energy storage (glyoxylate cycle, lipid metabolism, and glycogen production) was observed in old cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations